Fulminant myocarditis owing to high-dose interleukin-2 therapy for metastatic melanoma - Thavendiranathan, P (The British Institute of Radiology., 2011)
High-dose interleukin-2 (IL-2) therapy may cause acute myocarditis characterised by diffuse myocardial involvement and occasionally fulminant heart failure. Cardiac MRI (CMRI) provides a comprehensive assessment of myocardial function, inflammation and injury in a single examination and has shown value in the diagnosis of myocarditis. We report a case of a 54-year-old male with metastatic melanoma who developed acute severe myocarditis with fulminant heart failure after high-dose IL-2 therapy. CMRI using a combination of T(2) weighted imaging and T(1) weighted late post-gadolinium enhancement techniques played a key role in establishing the diagnosis. To our knowledge we present the first case report of the combined use of T(1) and T(2) weighted CMRI techniques to diagnose IL-2 induced myocarditis.